2012
DOI: 10.1128/aac.05147-11
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylenimine Is a Strong Inhibitor of Human Papillomavirus and Cytomegalovirus Infection

Abstract: Polyethylenimines are cationic polymers with potential as delivery vectors in gene therapy and with proven antimicrobial activity. However, the antiviral activity of polyethylenimines has not been addressed in detail thus far. We have studied the inhibitory effects of a linear 25-kDa polyethylenimine on infections with human papillomaviruses and human cytomegaloviruses. Preincubation of cells with polyethylenimine blocked primary attachment of both viruses to cells, resulting in a significant reduction of infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 56 publications
2
59
1
Order By: Relevance
“…In contrast to reports suggesting OBSL1 localization at the Golgi apparatus (65), no colocalization between the Golgi and OBSL1 was detected in HaCaT cells. Instead, we observed association of OBSL1 with the actin cytoskeleton, the tetraspanin CD151-both required for papillomavirus endocytosis-and colocalization of OBSL1 and L2 at the plasma membrane during HPV16 PsV entry, suggesting a role for OBSL1 in early events of HPV16 entry.…”
Section: Discussioncontrasting
confidence: 52%
See 3 more Smart Citations
“…In contrast to reports suggesting OBSL1 localization at the Golgi apparatus (65), no colocalization between the Golgi and OBSL1 was detected in HaCaT cells. Instead, we observed association of OBSL1 with the actin cytoskeleton, the tetraspanin CD151-both required for papillomavirus endocytosis-and colocalization of OBSL1 and L2 at the plasma membrane during HPV16 PsV entry, suggesting a role for OBSL1 in early events of HPV16 entry.…”
Section: Discussioncontrasting
confidence: 52%
“…Quantitative Western blot analysis demonstrated that siRNA-mediated OBSL1 depletion had no or a minor effect on initial HPV16 cell surface binding. As an internal control, HaCaT cells were transfected with control siRNA and treated with polyethyleneimine (PEI), a strong inhibitor for primary HPV16 PsV binding (65). These data were strengthened by results obtained from L1 surface staining by flow cytometry analysis (Fig.…”
Section: Hpv16 L2 Forms a Complex With Obsl1mentioning
confidence: 57%
See 2 more Smart Citations
“…The expression of the reporter is used as the readout for successful cell entry after delivery of the viral pseudogenome to the nucleus. Luciferase was used as the reporter in this study, and PsVs were prepared as described previously (14,15).…”
mentioning
confidence: 99%